2009
DOI: 10.1038/ng.394
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of testicular germ cell tumor

Abstract: We conducted a genome-wide association study for testicular germ cell tumor (TGCT), genotyping 307,666 SNPs in 730 cases and 1,435 controls from the UK and replicating associations in a further 571 cases and 1,806 controls. We found strong evidence for susceptibility loci on chromosome 5 (per allele OR = 1.37 (95% CI = 1.19-1.58), P = 3 × 10 −13 ), chromosome 6 (OR = 1.50 (95% = CI = 1.28-1.75), P = 10 −13 ) and chromosome 12 (OR = 2.55 (95% CI = 2.05-3.19), P = 10 −31 ). KITLG, encoding the ligand for the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
306
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(323 citation statements)
references
References 19 publications
15
306
1
1
Order By: Relevance
“…Testicular cancer is the most common malignancy affecting young men (3), more than 90% of testicular cancers result from TGCTs (4), TGCTs rank third in heritability among all cancers (5), and family history is the strongest known risk factor with a two-to sixfold increase among sons and a 5-to 19-fold increase among brothers of affected individuals (6)(7)(8)(9). Despite the strong evidence for heritability, the only TGCT susceptibility factors identified in genome-wide association studies are the gr/gr deletion on the Y chromosome and autosomal variants in KITLG, SPRY4, BAK1, and DMRT1, which together account for less than 10% of risk (10)(11)(12)(13)(14). The substantial difference in prevalence between sons and brothers of cases and the epidemiological evidence for maternal estrogens, birth order, birth weight, and other factors (15)(16)(17) together raise the possibility that maternal conditions, epigenetic effects, and perhaps unconventional modes of inheritance also contribute to TGCT risk (18).…”
mentioning
confidence: 99%
“…Testicular cancer is the most common malignancy affecting young men (3), more than 90% of testicular cancers result from TGCTs (4), TGCTs rank third in heritability among all cancers (5), and family history is the strongest known risk factor with a two-to sixfold increase among sons and a 5-to 19-fold increase among brothers of affected individuals (6)(7)(8)(9). Despite the strong evidence for heritability, the only TGCT susceptibility factors identified in genome-wide association studies are the gr/gr deletion on the Y chromosome and autosomal variants in KITLG, SPRY4, BAK1, and DMRT1, which together account for less than 10% of risk (10)(11)(12)(13)(14). The substantial difference in prevalence between sons and brothers of cases and the epidemiological evidence for maternal estrogens, birth order, birth weight, and other factors (15)(16)(17) together raise the possibility that maternal conditions, epigenetic effects, and perhaps unconventional modes of inheritance also contribute to TGCT risk (18).…”
mentioning
confidence: 99%
“…Another possibility is related to the presence of possible confounding risk factors. In fact, both GWAS included subjects with familial history of TGCT and personal history of cryptorchidism (Kanetsky et al 2009, Rapley et al 2009), which represent to date the most important clinical risk factor for TGCT with a relative risk of 4.8 (Dieckmann & Pichlmeier 2004). On the contrary, they did not consider another important risk factor for TGCT, infertility, or low sperm count.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, four genome-wide association studies (GWAS) from UK and USA have reported association of TGCTs with six new loci (KITLG, SPRY4, BAK1, DMRT1, TERT, and ATF7IP; Kanetsky et al 2009, Rapley et al 2009, Turnbull et al 2010. The strongest association for TGCT susceptibility was found for SNPs in KITLG (ligand for the membrane-bound receptor tyrosine kinase KIT) gene with a O2.5-fold increased risk of disease per major allele (Kanetsky et al 2009, Rapley et al 2009, which is the highest reported for any cancer to date (Chanock 2009). The KITLG-KIT system regulates the survival, proliferation, and migration of primordial germ cells (PGCs; Runyan et al 2006, Boldajipour & Raz 2007, the cells from which spermatogonia and spermatocytes develop and from which TGCT is believed to arise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KILTG gene encodes the ligand for the membrane receptor tyrosine kinase (c-KIT), and both the somatic and germline mutations in the KIT/ KILTG pathway have been well-linked to testicular cancer. 101,102 The results are notable because it is rare to find common risk alleles (in the context of SNPs) with ORs larger than 2, not only in cancers but also in other complex diseases.…”
Section: The Recent 2 Years: 2008 and 2009mentioning
confidence: 99%